Changes in circulating microRNA-126 levels are associated with immune imbalance in children with acute asthma. (May 2018) - Tian, Man; Ji, Yong; Wang, Tingting; Zhang, Wenxin; Zhou, Ying; Cui, Yubao
Regulation of the immune response in asthma is complex. MicroRNA-126 (miR-126) expression has been implicated in this response, so we sought to determine the clinical significance of miR-126 measured in the peripheral blood. A total of 80 children with acute asthma were selected to participate in the study and were compared to 80 healthy children. The relative circulating miR-126 levels, interleukin (IL)-4 levels, and the Th17 cell percentage in the peripheral blood of children in the case group were significantly higher than those in the control group, while the interferon (IFN)-γ levels and the CD4 + CD25 + Treg cell percentage were significantly lower than those in the control group. Along with the aggravation of the disease, the relative levels of miR-126 and IL-4 and the percentage of Th17 cells increased gradually, while the IFN-γ levels and the CD4 + CD25 + Treg cell percentage decreased. The relative level of miR-126 in the peripheral blood of children with asthma was positively correlated with IL-4 and the Th17 cell percentage and was negatively correlated with IFN-γ levels, CD4 + CD25 + Treg cell percentage and lung function indicators. The relative level of miR-126 was correlated with the Th17 cell percentage in the peripheral blood, forced vital capacity (FVC), and forced expiratory flow (FEF)75% of the children with asthma. The relative levels of miR-126 and IL-4 and the Th17 cell percentage were positively correlated with the severity of the asthma, while IFN-γ levels and the CD4 + CD25 + Treg cell percentage were negatively correlated with the severity of the asthma. CD4 + CD25 + Treg cell percentage and relative miR-126 levels were of the most predictive value in the diagnosis of asthma. Our findings show that the overexpression of miR-126 in acute asthma is correlated with signs of immune imbalance and is predictive of the severity of the disease, suggesting that it could be used as a potential serological marker for asthma diagnosis and evaluation.